Toward classification criteria for early osteoarthritis of the knee - Luyten, F; Bierma-Zeinstra, S; Dell'Accio, F; Kraus, V; Nakata, K; Sekiya, I; Arden, N; Lohmander, L (Elsevier, 2017)
Objective: To propose draft classification criteria for early stage osteoarthritis (OA) of the knee for use in a primary care setting. Methods: A group of basic scientists, physician-scientists, rheumatologists, orthopedic surgeons and physiotherapists in a workshop setting discussed potential classification criteria for early osteoarthritis of the knee. The workshop was divided into sessions around relevant topics with short state of the art presentations followed by breakout sessions, consensus discussions, and consolidation into a consensus document. Results: Three classes of criteria were agreed: 1. Pain, symptoms/signs, self-reported function and quality of life using tools such as KOOS: scoring ≤85% in at least 2 out of these 4 categories; 2. Clinical examination: at least 1 present out of joint line tenderness or crepitus ; 3. Knee radiographs: Kellgren & Lawrence (KL) grade of 0 or 1. MRI is at present not recommended as an aid to identify or define early OA in routine clinical practice or primary care, in light of the absence of validated consensus criteria and the high population prevalence of structural joint changes detected by this method. Biomarkers may have future utility in early OA classification, but no individual or set of biomarkers is yet robust enough. Conclusion: Based on our consensus proposal, draft classification criteria for early OA of the knee for use in clinical studies should include patient reported outcomes such as pain and function, together with clinical signs and KL grade 0-I on radiographs.